2021
DOI: 10.1007/s11738-021-03268-4
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth, ion accumulation, and antioxidant enzymes of endophyte-infected and endophyte-free tall fescue to salinity stress

Abstract: Endophyte-mediated salinity tolerance is largely unknown in tall fescue [Schedonorus arundinaceus (Schreb.)]. The experiment was designed to characterize growth, ion accumulation, and antioxidant metabolism of tall fescue infected by the endophyte Epichloë coenophiala to different levels of salinity stress. Endophyte-infected (E +) and endophyte-free (E−) tall fescue (cv Kentucky 31) plants were exposed to 10 d of 0 (unstressed control), 100 and 200 mM NaCl treatments in a greenhouse, respectively. Salinity st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…SOD, POD and CAT activity was higher in the EI plants compared to the EF plants under Al stress, which is consistent with our previous study on the endophyte-infected rice under Cd stress [20]. Pan et al also reported that endophytic infection increased antioxidant enzyme activity in tall fescue under salinity stress [36]. Plants combat the adverse effects of stress by increasing the activity of antioxidant enzymes [37].…”
Section: Discussionsupporting
confidence: 89%
“…SOD, POD and CAT activity was higher in the EI plants compared to the EF plants under Al stress, which is consistent with our previous study on the endophyte-infected rice under Cd stress [20]. Pan et al also reported that endophytic infection increased antioxidant enzyme activity in tall fescue under salinity stress [36]. Plants combat the adverse effects of stress by increasing the activity of antioxidant enzymes [37].…”
Section: Discussionsupporting
confidence: 89%
“…However, this can limit the entry of CO 2 and its assimilation (Seifikalhor et al, 2019). Despite that, the increases in Fv and Fw indicate full operation of the PSII reaction centers and stability of the photosynthetic apparatus under water restrictions (Pan et al, 2021). The values in Figure 2C suggest no photoinhibition damage to the PSII in yellow passion fruit seedlings treated with liquid fertilizers, as the range from 0.75 to 0.85 indicates optimal functioning of the photosynthetic apparatus (Ramos et al, 2022).…”
Section: Resultsmentioning
confidence: 98%
“…Irrigation with high-salinity water leads to a gradual accumulation of salts in substrates, thereby compromising the stabilization and productivity of yellow passion fruit seedlings (Bezerra et al, 2014). A quality decline in seedlings is attributed to osmotic factors, as roots struggle to absorb water from substrate, and ionic factors, causing nutritional imbalances and specific toxicity, especially due to sodium (Na + ) and chloride (Cl -) ions (Zörb et al, 2019;Arif et al, 2020;Pan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…While general climatic conditions affect the overall fitness of the genotypes, specific environmental factors likely condition the yearly alkaloid levels, as seen in the ergot alkaloid levels observed between years in the current study. It is well documented that abiotic factors such as pasture management, fertilization and water availability influence the accumulation of the different alkaloids [49][50][51][52][53][54]. Simultaneously, the presence of the endophyte has also been demonstrated to change the physiological and metabolic profile of plants harboring endophytes when compared to endophyte-free plants [51,[55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%